Applying fuzzy proportional integral derivative on Internet of things for figs greenhouse - Andi Riansyah; Sri Mulyono; M. Roichani (IAES International Journal of Artificial Intelligence (IJ-AI), 2021)
Indonesia is an agrarian country where most of population work as farmers. Various planting media have been developed in Indonesia such as using greenhouses. Greenhouse is one of very promising planting media for plant cultivators, because it can be a solution to challenges of extreme climate change. In a greenhouse, the state of the room can be easily controlled using technologies such as automatic watering systems, air temperature control, air humidity and soil moisture. This research focuses on figs by applying fuzzy proportional integral derivative (FPID) as artificial intelligence on the Internet of things (IoT) for greenhouses. It uses Tsukamoto method serves to monitor air conditions and soil conditions and then it is coupled with proportional integral derivative (PID) control to control air temperature, air humidity, and soil moisture so that it is always in the ideal condition of figs in greenhouse. By implementing FPID on IoT for greenhouse, the development of figs in greenhouse can be optimized because air and soil conditions can be maintained in ideal conditions.